2021
DOI: 10.1101/2021.07.20.21260871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asthma and the Risk of SARS-CoV-2 Infection Among Children and Adolescents

Abstract: Importance: More than 4 million SARS-COV-2 infections have occurred among children and adolescents in the United States. Risk factors for SARS-CoV-2 infection among children remain poorly defined. Objective: To evaluate the association between asthma and the risk of SARS-CoV-2 infection among children. Design: Retrospective cohort study Setting: A large, integrated health system in central North Carolina. Participants: Children 5 to 17 years of age with a Durham County address and at least one health care enco… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Although asthma is the most common chronic disease in children, there is a paucity of data on whether childhood asthma has increased the risk of SARS-CoV-2 infection or the severity of COVID-19. 4,17 Interestingly, in a recent retrospective cohort study, Rao et al 16 showed that children with asthma have a similar risk of SARS-CoV-2 infection compared to children without asthma. However, Shi et al 15 reported that school-age children with asthma with recent hospitalization or two or more courses of oral corticosteroids are at a significantly increased risk of hospitalization related to COVID-19.…”
Section: Asthma Cohortmentioning
confidence: 99%
See 2 more Smart Citations
“…Although asthma is the most common chronic disease in children, there is a paucity of data on whether childhood asthma has increased the risk of SARS-CoV-2 infection or the severity of COVID-19. 4,17 Interestingly, in a recent retrospective cohort study, Rao et al 16 showed that children with asthma have a similar risk of SARS-CoV-2 infection compared to children without asthma. However, Shi et al 15 reported that school-age children with asthma with recent hospitalization or two or more courses of oral corticosteroids are at a significantly increased risk of hospitalization related to COVID-19.…”
Section: Asthma Cohortmentioning
confidence: 99%
“…Therefore, the relationship between COVID‐19 and asthma is still unclear 13,14 . Moreover, in the pediatric setting, most studies are from high‐income countries, often with a small sample size, which may limit the generalizability of findings 15–17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation